Stress‐related suppression of peripheral cytokines predicts future relapse in alcohol‐dependent individuals with and without subclinical depression. (17th November 2019) - Fox, Helen C.; Milivojevic, Verica; MacDougall, Alicia; LaVallee, Heather; Simpson, Christine; Angarita, Gustavo A.; Sinha, Rajita
Abstract: Chronic alcohol abuse and depressive symptoms are both associated with peripheral cytokine changes. Despite this, cytokine adaptations have not been assessed in co‐morbid populations or prospectively as predictors of relapse. We examine cytokine responses to stress in alcohol‐dependent individuals and social drinkers, both with and without subclinical depression. We also examine the potential link between cytokine adaptations in response to stress and prospective alcohol relapse risk. Thirty‐three, alcohol‐dependent individuals (21 with and 12 without high depressive symptoms) and 37 controls (16 with and 21 without high depressive symptoms) were exposed to two 5‐minute personalized guided imagery conditions (stress and neutral) across consecutive days in a randomized and counterbalanced order. Alcohol craving and serum measures of tumor necrosis factor alpha (TNFα), tumor necrosis factor receptor 1 (TNFR1), interleukin‐6 (IL‐6), and interleukin‐1 receptor antagonist (IL‐1ra) were collected prior to and following imagery exposure. Following treatment discharge, follow‐up interviews were conducted over 90 days to assess relapse. Dampened IL‐1ra and IL‐6 in response to stress was observed as a function of alcohol dependence and not moderated by depressive symptoms. Lower levels of IL‐6 following stress also predicted greater drinking days following treatment. Conversely, high depressive symptomatology was associated solely with pro‐inflammatory adaptations. Stress‐related suppression of TNFα predicted drinking severity only in alcohol‐dependent individuals with subclinical depression, and suppressed TNFR1 following stress was only seen in individuals with subclinical depression. Stress‐induced suppression of pro‐inflammatory TNF markers may indicate a risk factor for alcohol‐dependent individuals with co‐occurring depressive symptoms.